Content Analysis of Islamic Communication Principles in the Film Air Mata di Ujung Sajadah - Ihsan Marzuki Nasution; Marlina Marlina (PT Agung Media Publisher, 2025)
This study analyzes how the film Air Mata di Ujung Sajadah presents Islamic communication principles and identifies dialogues that contradict them. Using a qualitative descriptive approach and content analysis based on Miles and Huberman's framework, the research examines six key principles: qaulan sadida, qaulan layyina, qaulan ma’rufa, qaulan karima, qaulan maysura, and qaulan baligha. The findings highlight the film's representation of ethical and moral values in Islamic communication within a religious-themed narrative. The findings indicate that the film effectively integrates Islamic communication principles, making it a potential medium for social learning through message observation, aligning with Melvin DeFleur’s Social Learning Theory. The interaction between characters frequently reflects Islamic communication values. Specifically, qaulan sadida appears 8 times, qaulan layyina 4 times, qaulan ma’rufa 9 times, qaulan karima 12 times, qaulan maysura 2 times, and qaulan baligha 5 times. Despite the strong representation of Islamic communication principles, the study also identifies dialogue that contradicts these values. Instances of qaulan sadida being violated through dishonesty appear 6 times, harsh speech contradicting qaulan layyina occurs 5 times, disrespectful words opposing qaulan karima appear 5 times, and inappropriate words conflicting with qaulan ma’rufa are also found 5 times. These findings suggest that while the film promotes Islamic communication ethics, it also depicts real-life conflicts that challenge these principles, reflecting the complexities of social interactions.